Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - Chapter Review Exercises - Page 164: 54


$$ H'(2)= -12+45=33.$$

Work Step by Step

Given $ H(x)=f(x)g(x)$, then we have $ H'(x)=f'(x)g(x)+f(x)g'(x)$ and hence $$ H'(2)=f'(2)g(2)+f(2)g'(2)=-3(4)+5(9)=-12+45=33.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.